2015
DOI: 10.1515/commun-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

The sociodemographics of political public deliberation: Measuring deliberative quality in different user groups

Abstract: Governments and local administrations increasingly use the internet to improve citizens' participation in deliberation processes. However, research studies have pointed out that deliberation outcomes vary due to the participants' sociodemographic differences. In this paper, we address this debate by quantitatively measuring different sociodemographic participant groups' deliberation quality. By building an index of the quality of understanding (IQU), we analyze the quality of 1,991 postings on local political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Media and internet use, especially that of SNSs, were found to mediate this relationship (Gil de Zúñiga, Jung, and Valenzuela, 2012;Xenos and Moy, 2007). This is not surprising as recent studies on internet use refer to a general shift from a first-level digital divide on physical internet access to a second-level or participation divide based on socio-demographic variables (e.g., age, sex, educational attainment; e.g., Klinger and Russmann, 2015) as well as internet skills and use (Brake, 2014;Min, 2010;van Deursen and van Dijk, 2011). Hence, one might expect users with a high interest in and knowledge about climate change as well as more frequent (online) media use to be more likely to engage in the online discourse.…”
Section: Online Engagementmentioning
confidence: 83%
“…Media and internet use, especially that of SNSs, were found to mediate this relationship (Gil de Zúñiga, Jung, and Valenzuela, 2012;Xenos and Moy, 2007). This is not surprising as recent studies on internet use refer to a general shift from a first-level digital divide on physical internet access to a second-level or participation divide based on socio-demographic variables (e.g., age, sex, educational attainment; e.g., Klinger and Russmann, 2015) as well as internet skills and use (Brake, 2014;Min, 2010;van Deursen and van Dijk, 2011). Hence, one might expect users with a high interest in and knowledge about climate change as well as more frequent (online) media use to be more likely to engage in the online discourse.…”
Section: Online Engagementmentioning
confidence: 83%
“…Turning to potential differences in deliberative discussion quality according to gender, previous findings are mixed. Several studies have found no gender gap in terms of deliberative quality (Klinger and Russmann 2015;Grunenfelder and Bächtiger 2007;Himmelroos 2017;. Nevertheless, a study by Afsahi (2020) indicates that women can display a higher capacity to engage in deliberative behavior compared to men.…”
Section: Deliberative Quality In Mixed Deliberation According To Status and Gendermentioning
confidence: 99%
“…Other indices and frameworks have been proposed, but they still rely on (a subset of) similar dimensions. For instance, Klinger and Russmann (2015) have investigated citizens' participation in deliberation processes by proposing an index of the quality of understanding that includes dimensions about statements of reasons, proposals for solutions, respect, doubts and reciprocity. Other studies have developed a more comprehensive framework that accounts for the multifaceted concept of deliberation.…”
Section: Existing Measures Of Debate Qualitymentioning
confidence: 99%